Pelton Turbine Design Overview (Proceedings of Faculty of Civil Engineering, 2021)
This paper presents an overview of Pelton turbine design. Since very complex flow conditions and physical processes occur during the operation of the turbine, the optimization and design of such a system is, consequently, a challenge. There are several different formulas and recommendations for design and optimization. Therefore, the aim of this paper was to consolidate them and give an overview in one place. The research for the purposes of this paper arose from the previous research for a master thesis.
Keywords: Pelton turbine; design; nozzle; Pelton wheel; bucket